CCM2 Modeling of the Effect of Tibetan Plateau on the Distribution of Arid and Semi-arid Areas and their Vegetation in East Asia - Chen, Xiongwen; Zhang, Xin Shi (Annals of Arid Zone, 2016)
Studying the causes for the unique distribution of arid and semi-arid areas in East Asia is important for land management and environmental restoration in this region. The distribution of arid and semi-arid areas and their associated vegetation in East Asia (15Â°N-60oN, 60oE-1500E) were constructed by Geographic Information System and the climatic data set produced by the CCM2 of NCAR with Tibetan Plateau and without Tibetan Plateau (the elevation was assumed to decrease to 1000 m and equal to its surroundings). If there were no Tibetan Plateau, the distribution of arid and semi-arid areas and their vegetation in East Asia would change significantly. The moist and semi-moist areas would increase by about 3.53% and 0.86%, respectively; but the semi-arid and arid areas would decrease by about 2.01 % and 2.39%, respectively. The areas of Tropical Thorn Woodland, Warm Temperate Meadow, Subtropical Desert and Warm Temperate Desert would decrease dramatically. The area of Savannah (subtropical grass and scrub) would increase by about 139.7%. Tibetan Plateau has deeply influenced the distribution of arid and semi-arid areas in many surrounding countries. Western China and Mongolia would be less dry if there were no Tibetan Plateau.